Method for producing chalcogenide glass material

JP7939622B2Active Publication Date: 2026-10-22NIPPON ELECTRIC GLASS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024169004
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-03-28
Filing Date
2024-09-27
Publication Date
2026-10-22
Estimated Expiration
2038-10-17

AI Technical Summary

Benefits of technology

【0018】 本発明によれば、赤外線透過率に優れ、赤外線センサの光学素子として好適なカルコゲナイドガラス材を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007939622000005
    Figure 0007939622000005
  • Figure 0007939622000001
    Figure 0007939622000001
  • Figure 0007939622000002
    Figure 0007939622000002
Patent Text Reader

Abstract

To provide a glass that has excellent infrared transmittance and is suitably used for an infrared sensor.SOLUTION: A chalcogenide glass material has an oxygen content of 100 ppm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a chalcogenide glass material used for infrared sensors, infrared cameras and the like.

Background Art

[0002] Automotive night vision systems, security systems and the like are equipped with infrared sensors used for living body detection at night. Since the infrared sensor senses infrared rays with a wavelength of about 8 to 14 μm emitted from a living body, optical elements such as filters and lenses that transmit infrared rays in the relevant wavelength range are provided in front of the sensor unit.

[0003] Examples of materials for the optical elements as described above include Ge and ZnSe. Since these are crystalline bodies, they have poor workability and are difficult to process into complex shapes such as aspherical lenses. This leads to problems that mass production is difficult, and miniaturization of infrared sensors is also difficult.

[0004] Accordingly, chalcogenide glass has been proposed as a vitreous material that transmits infrared rays with a wavelength of about 8 to 14 μm and is relatively easy to process. (See, for example, Patent Document 1)

Prior Art Documents

Patent Documents

[0005]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0006] The glass described in Patent Document 1 has a significantly reduced infrared transmittance at a wavelength of 10 μm or more, and thus is particularly inferior in sensitivity to infrared rays emitted from living bodies, which may cause the infrared sensor to fail to function sufficiently.

[0007] In view of the above, the present invention aims to provide glass that has excellent infrared transmittance and is suitable for infrared sensor applications. [Means for solving the problem]

[0008] The inventors, after conducting various studies, obtained the following findings and proposed the present invention. Chalcogenide glass is usually manufactured by placing raw materials in a quartz tube, evacuating it, and then melting it in a sealed state. However, even when using high-purity raw materials, the surface of the raw materials is oxidized, and oxygen is mixed into the glass as an impurity, and the oxygen combines with the components in the glass. As a result, this bonding has an absorption peak in the infrared region, which tends to reduce infrared transmittance.

[0009] In other words, the chalcogenide glass material of the present invention is characterized by having an oxygen content of 100 ppm or less. By regulating the oxygen content, which causes a decrease in infrared transmittance, absorption in the infrared region becomes less likely to occur, and the decrease in infrared transmittance can be suppressed.

[0010] The chalcogenide glass material of the present invention preferably contains more than 0 to 100% Te+S+Se.

[0011] The chalcogenide glass material of the present invention preferably contains 20-90% Te in mol%.

[0012] The chalcogenide glass material of the present invention preferably contains more than 0 to 50% of Ge+Ga+Sb+As in mol%.

[0013] The chalcogenide glass material of the present invention preferably contains 0 to 50% Ag in mol%.

[0014] The chalcogenide glass material of the present invention preferably contains 0 to 50% Si by mol%.

[0015] In the present invention, it is preferable that the chalcogenide glass material does not contain striations longer than 500 μm.

[0016] The optical element of the present invention is characterized by using the above-mentioned chalcogenide glass material.

[0017] The infrared sensor of the present invention is characterized by using the above-mentioned optical element. [Effects of the Invention]

[0018] According to the present invention, it is possible to provide a chalcogenide glass material that has excellent infrared transmittance and is suitable as an optical element for an infrared sensor. [Brief explanation of the drawing]

[0019] [Figure 1] This graph shows the infrared transmittance curves for Example 1 and Comparative Example 1. [Modes for carrying out the invention]

[0020] The chalcogenide glass material of the present invention has an oxygen content of 100 ppm or less, preferably 50 ppm or less, 20 ppm or less, 15 ppm or less, 12 ppm or less, 10 ppm or less, 8 ppm or less, 5 ppm or less, 3 ppm or less, and particularly preferably 1 ppm or less. If the oxygen content is too high, absorption in the infrared region is likely to occur, and the infrared transmittance tends to decrease. The lower limit of the oxygen content is not particularly limited, but in reality it is 0.01 ppm or more.

[0021] The bonding areas between oxygen and components in the glass are prone to changes in refractive index and tend to form striations. However, because the chalcogenide glass material of the present invention has a low oxygen content, the oxygen does not readily bond with the components in the glass, making striations less likely to occur. Specifically, it is preferable that the chalcogenide glass material of the present invention does not contain striations longer than 500 μm. Even if striations are present in the chalcogenide glass material, their length is preferably less than 500 μm, 200 μm or less, 100 μm or less, 50 μm or less, and particularly 10 μm or less. In this way, when used as an optical element, a decrease in resolution caused by image distortion and irregularities can be suppressed.

[0022] Since the chalcogenide glass material of the present invention has a low oxygen content as described above, oxygen is less likely to bind to components in the glass. Specifically, Ge-O bonds (13.0 μm), Se-O bonds (11.0 μm), As-O bonds (12.7 μm), Si-O bonds (8.9 μm, 14.2 μm), Ga-O bonds (17.5 μm) and the like, which have absorption peaks in the infrared region, are less likely to be generated, so that a decrease in infrared transmittance can be easily suppressed.

[0023] Hereinafter, the composition of the chalcogenide glass material of the present invention will be described. In the following description of the content of each component, "%" means "mol%" unless otherwise specified.

[0024] Te, S and Se, which are chalcogen elements, are components that form a glass skeleton. The content of Te+S+Se (the total amount of Te, S and Se) is preferably more than 0 to 100%, 20 to 90%, 30 to 80%, 40 to 85%, 45 to 82%, 50 to 80%, 55 to 80%, 60 to 80%, 65 to 80%, and particularly preferably 70 to 80%. If the content of Te+S+Se is too low, vitrification becomes difficult. If the content of Te+S+Se is too high, evaporation of glass components tends to occur during melting, which easily causes striae. From the viewpoint of suppressing the occurrence of such defects, the content of Te+S+Se is preferably 90% or less.

[0025] In addition, preferable ranges of the contents of Te, S and Se are as follows.

[0026] Among Te, S and Se, Te is the most preferable because it enables infrared transmission up to longer wavelengths. The content of Te is preferably 20 to 90%, 30 to 88%, 40 to 85%, 45 to 82%, 50 to 80%, 55 to 80%, 60 to 80%, 65 to 80%, and particularly preferably 70 to 80%. If the content of Te is too low, vitrification becomes difficult. On the other hand, if the content of Te is too high, Te-based crystals precipitate, making it difficult for infrared rays to pass through.

[0027] The S content is preferably 0-90%, 10-90%, 20-88%, 30-85%, 40-82%, 50-80%, 55-80%, 60-80%, 65-80%, and particularly 70-80%.

[0028] The Se content is preferably 0-90%, 10-90%, 20-88%, 30-85%, 40-82%, 50-80%, 55-80%, 60-80%, 65-80%, and particularly 70-80%.

[0029] Ge, Ga, Sb, and As are components that broaden the vitrification range and enhance the thermal stability (vitrification stability) of the glass. The Ge+Ga+Sb+As content (total amount of Ge, Ga, Sb, and As) is preferably between 0 and 50%, 10 and 45%, 15 and 43%, 20 and 43%, and especially between 30 and 43%. If the Ge+Ga+Sb+As content is too low or too high, vitrification becomes difficult.

[0030] Furthermore, the Ge+Ga content (total amount of Ge and Ga) is preferably 0-40%, 2-35%, 4-33%, 4-30%, 4-28%, and particularly preferably 4-25%. The Sb+As content (total amount of Sb and As) is preferably 0-45%, 5-40%, 10-35%, 15-35%, and particularly preferably 20-35%.

[0031] The preferred ranges for the content of Ge, Ga, Sb, and As are as follows:

[0032] The Ge content is preferably 0-40%, 2-35%, 4-33%, 4-30%, 4-28%, and particularly preferably 4-25%.

[0033] The Ga content is preferably 0-40%, 2-35%, 4-33%, 4-30%, 4-28%, and particularly preferably 4-25%.

[0034] The Sb content is preferably 0-45%, 5-40%, 10-35%, 15-35%, and particularly preferably 20-35%.

[0035] The As content is preferably 0-45%, 5-40%, 10-35%, 15-35%, and particularly 20-35%.

[0036] Ag is an essential component that enhances the thermal stability (vitrification stability) of glass. The preferred Ag content is 0-50%, over 0-50%, 1-45%, 2-40%, 3-35%, 4-30%, 5-25%, and especially 5-20%. Too much Ag content makes vitrification difficult.

[0037] Si is an essential component that enhances the thermal stability (vitrification stability) of glass. The Si content is preferably 0-50%, over 0-50%, 1-45%, 2-40%, 3-35%, 4-30%, 5-25%, and especially preferably 5-20%. If the Si content is too high, infrared absorption due to Si is more likely to occur, making it difficult for infrared rays to pass through.

[0038] Al, Ti, Cu, In, Sn, Bi, Cr, Sb, Zn, and Mn are components that enhance the thermal stability (vitrification stability) of glass without reducing its infrared transmission properties. The content of Al+Ti+Cu+In+Sn+Bi+Cr+Sb+Zn+Mn (the total amount of Al, Ti, Cu, In, Sn, Bi, Cr, Sb, Zn, and Mn) is preferably 0-40%, 2-35%, 4-30%, and particularly 5-25%. If the content of Al+Ti+Cu+In+Sn+Bi+Cr+Sb+Zn+Mn is too high, vitrification becomes difficult. The content of each component Al, Ti, Cu, In, Sn, Bi, Cr, Sb, Zn, and Mn is preferably 0-40%, 1-40%, 1-30%, 1-25%, and particularly 1-20%, respectively. Among these, Al, Cu, or Sn are preferred because they have a particularly significant effect in improving the thermal stability of the glass.

[0039] F, Cl, Br, and I are also components that enhance the thermal stability (vitrification stability) of glass. The content of F+Cl+Br+I (total amount of F, Cl, Br, and I) is preferably 0-40%, 2-35%, 4-30%, and especially 5-25%. If the content of F+Cl+Br+I is too high, vitrification becomes difficult and weather resistance tends to decrease. The content of each component of F, Cl, Br, and I is preferably 0-40%, 1-40%, 1-30%, 1-25%, and especially 1-20%, respectively. Among these, I is preferred because it can be used as an elemental raw material and has a particularly large effect in enhancing the thermal stability of glass.

[0040] Furthermore, in addition to the above-mentioned components, P, Pb, Tl, etc. may be included to the extent that they do not impair the effects of the present invention. Specifically, the content of each of these components is preferably 0 to 5%, and more preferably 0 to 2%.

[0041] The chalcogenide glass material of the present invention can be manufactured, for example, as follows: Mix the raw materials to obtain a raw material batch to achieve the above glass composition. Next, evacuate the quartz glass ampoule while heating it, then place the raw material batch inside and seal the quartz glass ampoule with an oxygen burner while introducing a reducing gas into the quartz glass ampoule. Next, heat the sealed quartz glass ampoule in a melting furnace at a rate of 10-40°C / hour to 650-1000°C and hold for 6-12 hours. During the holding time, if necessary, invert the quartz glass ampoule to stir the molten material. In this way, by melting the raw materials in a reducing gas, oxygen in the raw materials is removed, making it easier to obtain glass with a low oxygen content. Here, as the reducing gas, N2-H2 mixed gas, CO, H2S, N2O, SO2, NH3, etc. can be used, but it is preferable to use N2-H2 mixed gas because it is inexpensive and highly safe.

[0042] Next, the quartz glass ampoule is removed from the melting furnace and rapidly cooled to room temperature in a reducing gas to obtain the chalcogenide glass material of the present invention.

[0043] Furthermore, by creating a reducing gas atmosphere inside the melting furnace, quartz glass ampoules can be melted without sealing them, making it possible to continuously melt glass with a low oxygen content.

[0044] Alternatively, a reducing gas can be bubbling into the molten glass. Bubbling agitates the glass, promoting its homogenization. As a result, the formation of striations can be suppressed.

[0045] By processing the chalcogenide glass material obtained in this way into a predetermined shape (disk shape, lens shape, etc.), an optical element can be manufactured.

[0046] To improve transmittance, an anti-reflective coating may be formed on one or both sides of the optical element. Methods for forming the anti-reflective coating include vacuum deposition, ion plating, and sputtering.

[0047] It is also acceptable to form an anti-reflective coating on the chalcogenide glass material and then process it into a predetermined shape. However, since peeling of the anti-reflective coating is more likely to occur during the processing, it is preferable to form the anti-reflective coating on the chalcogenide glass material after processing it into a predetermined shape, unless there are special circumstances.

[0048] Because the chalcogenide glass material of the present invention has excellent infrared transmittance, it is suitable as a cover member for protecting the sensor part of an infrared sensor, or as an optical element such as a lens for focusing infrared light onto the infrared sensor. [Examples]

[0049] The present invention will be described below based on examples, but the present invention is not limited to these examples.

[0050] Tables 1-4 show Examples 1-35 and Comparative Example 1 of the present invention.

[0051] [Table 1]

[0052] [Table 2]

[0053] [Table 3]

[0054] [Table 4]

[0055] Samples for Examples 1-34 were prepared as follows: After evacuating a quartz glass ampoule while heating it, a batch of raw materials prepared to achieve the glass composition shown in the table was placed inside. Next, the quartz glass ampoule was sealed with an oxygen burner while introducing N2-H2 gas into it. Then, the sealed quartz glass ampoule was heated in a melting furnace at a rate of 10-40°C / hour to 650-1000°C and held for 6-12 hours. During the holding time, the quartz gas ampoule was inverted to agitate the molten material. Subsequently, the quartz glass ampoule was removed from the melting furnace and rapidly cooled to room temperature to obtain the sample.

[0056] The sample for Example 35 was prepared as follows: A batch of raw materials, prepared to have the glass composition shown in the table, was placed in a quartz glass ampoule. Next, the unsealed quartz glass ampoule was heated to 750°C at a rate of 40°C / hour in a melting furnace into which N2-H2 gas was introduced, and then held for 6 hours. Subsequently, the quartz glass ampoule was removed from the melting furnace and rapidly cooled to room temperature to obtain the sample.

[0057] Comparative Example 1 was prepared in the same manner as in Example 1, except that N2-H2 gas was not introduced.

[0058] The oxygen content of the obtained samples was measured using an oxygen analyzer (LECO Japan ONH836). Infrared transmittance was also measured at a thickness of 2 mm to confirm the presence or absence of absorption peaks in the infrared region. Furthermore, the obtained samples were internally observed using a shadowgraph method with infrared light at a wavelength of 10 μm to confirm the presence or absence of striations longer than 500 μm. The results are shown in Tables 1-4. The infrared transmittance curves for Example 1 and Comparative Example 1 are shown in Figure 1.

[0059] As is clear from Tables 1-4 and Figure 1, the samples of Examples 1-35 had low oxygen content in the glass (0.1-1.4 ppm) and no absorption peaks in the infrared region. Furthermore, no striations longer than 500 μm were observed, indicating excellent homogeneity.

[0060] On the other hand, the sample of Comparative Example 1 had an oxygen content of 123 ppm, and an absorption peak was present around 17.5 μm. Based on the location of the absorption peak, it is considered that the absorption peak was caused by Ga-O bonding. Furthermore, striations longer than 500 μm were observed. [Industrial applicability]

[0061] The infrared-transmitting glass of the present invention is suitable as a cover member for protecting the sensor portion of an infrared sensor, or as an optical element such as a lens for focusing infrared light onto the sensor portion.

Claims

1. A method for producing chalcogenide glass material, The process includes a step of introducing a batch of raw materials, which has been prepared to achieve a target glass composition, and a reducing gas into a quartz glass ampoule, sealing it, and then heating the quartz glass ampoule to melt the batch of raw materials in the reducing gas. The chalcogenide glass material has an oxygen content of 100 ppm or less and 0.01 ppm or more, and contains 20-90% Te and 2-40% Ga in mol%. A method for producing a chalcogenide glass material, characterized in that, in the melting step, the sealed quartz glass ampoule is heated in a melting furnace at a rate of 10 to 40°C / hour to 650 to 1000°C, and then held for 6 to 12 hours.

2. The method for producing a chalcogenide glass material according to claim 1, characterized in that the chalcogenide glass material contains 20 to 98% of Te + S + Se in mol% as a composition.

3. The method for producing a chalcogenide glass material according to claim 1 or 2, characterized in that the chalcogenide glass material contains 2 to 50% of Ge + Ga + Sb + As in mol%.

4. The method for producing a chalcogenide glass material according to any one of claims 1 to 3, characterized in that the chalcogenide glass material contains 0 to 50% Ag in mol%.

5. The method for producing a chalcogenide glass material according to any one of claims 1 to 4, characterized in that the chalcogenide glass material contains 0 to 50% Si in mol%.

6. The method for producing a chalcogenide glass material according to any one of claims 1 to 5, characterized in that the chalcogenide glass material does not contain striations of a length of 500 μm or more in the glass material.

7. The method for producing a chalcogenide glass material according to any one of claims 1 to 6, characterized in that the chalcogenide glass material does not have an absorption peak around a wavelength of 17.5 μm.

8. The method for producing a chalcogenide glass material according to claim 7, characterized in that the absorption peak near a wavelength of 17.5 μm is a peak caused by a Ga-O bond.

Citation Information

Patent Citations

  • Production of chalcogenide glass

    JP1988218518A

  • Production of clad glass tube for chalcogenide glass fiber

    JP1988230532A

  • Infrared-transmitting glass and production thereof

    JP1993004835A

  • Infrared transmitting glass for molding

    JP2009161374A

  • Infrared transmitting glass

    JP2017057110A